2022
DOI: 10.3389/fcimb.2022.820367
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study Reveals Host Microbial Determinants of Clinical Response to Fecal Microbiota Transplant Therapy in Type 2 Diabetes Patients

Abstract: BackgroundIncreasing evidence shows that alterations in gut microbiome (GM) contribute to the development of type 2 diabetes mellitus (T2DM), and fecal microbiota transplantation (FMT) successfully treats various human diseases. However, the benefits of FMT therapy to T2DM patients remain unknown.MethodsWe enrolled 17 patients with T2DM for nonblinded, one-armed intervention trial of FMT. A total of 20 healthy individuals were recruited as the baseline control. HbA1c% and metabolic parameter change were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…In addition, FMT, a process of transferring stool from a healthy donor or antidiabetes treatment subjects to mice, displayed a significant improvement in microbial composition and metabolic homeostasis ( 131 ). A prospective study revealed that FMT could bring benefits for the management of T2DM via modulating levels of certain microbiome such as Rikenellaceae and Anaerotruncus ( 132 ).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…In addition, FMT, a process of transferring stool from a healthy donor or antidiabetes treatment subjects to mice, displayed a significant improvement in microbial composition and metabolic homeostasis ( 131 ). A prospective study revealed that FMT could bring benefits for the management of T2DM via modulating levels of certain microbiome such as Rikenellaceae and Anaerotruncus ( 132 ).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Thirdly, FMT from normal glucose tolerance or antidiabetes treatment subjects to mice revealed a significant improvement in gut microbiota composition, glucose homeostasis, and metabolic health (17,124,172). Despite that this promising treatment was still in its infancy (173)(174)(175), FMT combined with antidiabetes drugs might bring novel interventions and perspectives in T2DM management. The effects and mechanisms underneath these potential treatment schedules are still unclear, and it is vital to further develop meaningful and applicable interventions combined with intestinal microbiota in the future study.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Most studies assessing the efficacy of FMT are conducted in animal models, with fewer studies in patients with T2DM. For example, a recent study evaluating clinical responses to FMT of 17 human participants, showed that 11 of them (64%) had statistically significant decrease in hemoglobin A1c (HbA1c) and blood glucose, while post-prandial C-peptide, a measure correlated with serum insulin, was elevated ( 46 ). Microbiota analysis revealed increases of the genus Anaerotruncu s, which has been associated with increased insulin resistance ( 47 ).…”
Section: Fecal Microbiota Transplant Effects On Diabetes and Metaboli...mentioning
confidence: 99%
“…Microbiota analysis revealed increases of the genus Anaerotruncu s, which has been associated with increased insulin resistance ( 47 ). The individuals harboring increased abundance of Anaerotruncu s exhibited a better clinical response to FMT intervention ( 46 ), indicating that this bacterial genus may be a marker of treatment efficacy in diabetics. Results from another recently conducted study indicated that FMT-induced gut microbiota changes were correlated with improvements in blood glucose in T2DM ( 48 ).…”
Section: Fecal Microbiota Transplant Effects On Diabetes and Metaboli...mentioning
confidence: 99%
See 1 more Smart Citation